Perceived Organizational Support and Reduced Job Performance During COVID-19 - Hasan, Naveed; Waseem, Muhammad Adnan; Sarfraz, Muddassar; Wajid, Nauman (Inquiry (Chicago), 2023)
Current research aims to identify a framework to enhance the performance of employees in government sector healthcare during the COVID-19 pandemic. Perceived organizational support was identified to enhance employees’ performance through the intervention of a psychological process containing 3 states, that is, psychological safety, felt obligation and organization-based self-esteem. Job performance is considered as planned behavior, and psychological links are developed on the basis of the theory of planned behavior. This study is quantitative and used an empirical survey. Respondents of the study were nursing staff of government hospitals in Pakistan. The data were collected during the first wave of COVID-19 in Pakistan through online distributed questionnaires, and the data were analyzed using Smart PLS. Results show that perceived organizational support positively affects job performance during the COVID-19 crisis, and all the psychological states mediate the relationship. The study results are helpful for decision-makers of public sector organizations dealing with the most common problem of performance reduction during COVID-19. Results are also helpful for policymakers to address reduced performance in most government hospitals. Future research should consider antecedents of the perception of organizational support in the context of government and private hospitals.